2018
DOI: 10.1111/mmi.13930
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of agonism and antagonism of the Pseudomonas aeruginosa quorum sensing regulator QscR with non‐native ligands

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that uses the process of quorum sensing (QS) to coordinate the expression of many virulence genes. During quorum sensing, N-acyl-homoserine lactone (AHL) signaling molecules regulate the activity of three LuxR-type transcription factors, LasR, RhlR and QscR. To better understand P. aeruginosa QS signal reception, we examined the mechanism underlying the response of QscR to synthetic agonists and antagonists using biophysical and structural approaches. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 66 publications
(142 reference statements)
1
26
0
Order By: Relevance
“…3). The more interesting result is that the PAS domain of VqmA was quite different from that of other characterized LuxR proteins (17)(18)(19)(20), but similar to that of some signal proteins of other non-LuxR family proteins ( Fig. 4 and Fig.…”
Section: Overall Structure Of the Vqma-dpo-dna Complexmentioning
confidence: 80%
See 2 more Smart Citations
“…3). The more interesting result is that the PAS domain of VqmA was quite different from that of other characterized LuxR proteins (17)(18)(19)(20), but similar to that of some signal proteins of other non-LuxR family proteins ( Fig. 4 and Fig.…”
Section: Overall Structure Of the Vqma-dpo-dna Complexmentioning
confidence: 80%
“…The DBD region was relatively conserved. We compared the DBD region of VqmA with several proteins with known structures of the LuxR family in sequence and three-dimensional conformation (17)(18)(19)(20)(21). The results showed that although VqmA and other LuxR family proteins were not very conservative in sequence, but they were consistent in three-dimensional conformation (Fig.…”
Section: Overall Structure Of the Vqma-dpo-dna Complexmentioning
confidence: 98%
See 1 more Smart Citation
“…Although our study is focused on the activation of AHL receptors, noncognate AHLs can also inhibit receptor activity through a variety of mechanisms (7, 15, 16, 18, 4144). To explore inhibitory effects of noncognate AHLs, we tested our AHL panel for inhibition of LasR, QscR, CviR, or LuxR activity.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the orphan P. aeruginosa LuxR-type receptor QscR contains such a loop (SI Appendix, Fig. S6), and QscR displays ligand promiscuity (37,38). Conversely, CviR and TraR display strict specificity for their cognate autoinducers (11,18,39,40).…”
Section: Homoserine Lactonementioning
confidence: 99%